Tokyo and IOC officials stress that Olympics are on despite coronavirus concerns (Japan Times, 2020)
Tokyo 2020 organizers reiterated their message Thursday at the start of two days of meetings with the International Olympic Committee: the Summer Games will not be waylaid by the coronavirus that is spreading from neighboring China.